Practical Standards for Holding Fair Elections - The 2009 Parliamentary Elections in the Kurdistan Region as a Model - Ahmed, Muhammad Mustafa (Journal of Legal and Political Studies, 2016)
Elections with results that reflect the will of voters can be described as free and clean. Accordingly, there are practical procedures and necessary conditions that must be present at any clean election. These procedures and conditions include providing for the citizen’s rights for voting and self-nomination; for the freedom of choice; for confidentiality in voting; for transparency in counting the votes; for an independent supervision of elections; for integrity in determining the electoral districts; and for the presence of local and international supervisors and analysts. Furthermore, a free election has to ensure the freedom of opinion, equality in opportunities for conducting election campaigns and propaganda for all parties, and impartiality of the state institutions vis-a-vis electoral competition. The 2009 parliamentary elections in the Kurdish region of Iraq, that had resulted in largely changing the political map of the region , was a clean election to the extent that it theoretically took place with a legal framework for conducting an election at place. Despite this, the elections in practice lacked integrity and did not meet many of the international criteria of a clean election which, at the end, negatively impacted upon the formation of the state institutions and their role in the Kurdish society.
Keywords: Fair Elections; Iraq; Parliamentary Elections; Kurdistan Region; Citizen; Voting; Selfnomination